The Empirical Analysis of Performance Management System : A Case Study of a University in South Africa - Ngcamu, Bethuel Sibongiseni (Journal of Economics and Behavioral Studies, 2013)
The absence of a single performance management system (PMS) aligned to institutional strategic plan often results in failure to deliver anticipated outcomes. This study aims to investigate the employees’ readiness on the forthcoming implementation of the PMS at the university concerned and diagnose impediments, thus providing pertinent recommendations on the bottlenecks identified.It is a great concern that universities fail to develop customised performance management systems which are aligned to university strategic plans that can be cascaded to faculties and departments.This study adopted a quantitative survey method, whereby a structured questionnaire was administered by the researcher to a selected population size of 150 of which 108 completed questionnaires generating a response rate of 72%. A reasonably high percentage (34.3%) of the respondents disagreed with the need for PMS in this university and a disproportionately high percentage of 49.1% of the respondents agreed that there is a dire need for such as the system will manipulate and enforce a particular agenda in its absence.The article presents an overview of factors that have a potential to hamper the successful implementation of the PMS in universities. The findings arrived in this study can inform and assist university leaders to consider all contributory factors on the ineffectivess of the PMS in universities during their planning phases.